2017
DOI: 10.15823/su.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Education System in Integrated Social Education Context

Abstract: 1 Lietuvos edukologijos universitetas, Studentų g. 39, 08106 Vilnius, giedre.kvieskiene@ 2 Lietuvos laisvosios rinkos institutas, Šeimyniškių g. 3A, 09312 Vilnius, marija@llri.lt Projekto numeris -2016-1-LT01-KA201-023232Anotacija. Socialinis ugdymas(is) -tai gebėjimas suprasti visuomenėje vykstančius p santykį ir poveikį sau, kitiems ir pasauliui 1 . Skurdas, vartotojiškumas, darbas, tarša, sveikata, migracija, socialiniai tinklai, balsavimas, propaganda -tai aštrios šių dienų kuriomis susiduria kiekvienas as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…the language barrier, the lack of suitable teaching materials, as well as the lack of skills among teachers working with these target groups (Djačkova et al, 2011: 10;; -the need to create a supportive environment, reducing the intolerance of teachers and the general society to foreigners and raising the awareness of the society about the opportunities and the potential that third-country nationals could bring to the future development of the state (Indāns, 2012; Pičukāne, 2013; Bartkevičiene & Raudelitinaite, 2012); -the lack of succession and continuity in the implementation of integration measures; the need for better cooperation between the society, the local authorities and the private sector (Kļave et al, 2015;Veebel, 2015); -the need for inter-cultural education, which should not concern only schools, but the whole society (Margeviča, 2008: 14;Trasberg & Kond, 2017, Szerlag, 2017; -the creation of a favourable learning environment where students could communicate, collaborate and feel safe (Pičukāne, 2013: 9;Rauhansalo & Kvieska, 2017). According to several national policy planning documents adopted in Latvia, it is intended to implement various measures aimed at improving the education quality of immigrant children like teaching basic Latvian language skills to newlyarrived immigrants, motivating Latvian schools to enrol the children of thirdcountry nationals and supporting the elaboration of additional education programmes for teaching the Latvian language to those children whose native language is not Latvian (Guidelines on National Identity, civil society and integration policy (2012-2018), 2011).…”
Section: Methodsmentioning
confidence: 99%
“…the language barrier, the lack of suitable teaching materials, as well as the lack of skills among teachers working with these target groups (Djačkova et al, 2011: 10;; -the need to create a supportive environment, reducing the intolerance of teachers and the general society to foreigners and raising the awareness of the society about the opportunities and the potential that third-country nationals could bring to the future development of the state (Indāns, 2012; Pičukāne, 2013; Bartkevičiene & Raudelitinaite, 2012); -the lack of succession and continuity in the implementation of integration measures; the need for better cooperation between the society, the local authorities and the private sector (Kļave et al, 2015;Veebel, 2015); -the need for inter-cultural education, which should not concern only schools, but the whole society (Margeviča, 2008: 14;Trasberg & Kond, 2017, Szerlag, 2017; -the creation of a favourable learning environment where students could communicate, collaborate and feel safe (Pičukāne, 2013: 9;Rauhansalo & Kvieska, 2017). According to several national policy planning documents adopted in Latvia, it is intended to implement various measures aimed at improving the education quality of immigrant children like teaching basic Latvian language skills to newlyarrived immigrants, motivating Latvian schools to enrol the children of thirdcountry nationals and supporting the elaboration of additional education programmes for teaching the Latvian language to those children whose native language is not Latvian (Guidelines on National Identity, civil society and integration policy (2012-2018), 2011).…”
Section: Methodsmentioning
confidence: 99%
“…There are other scientific analyses about the significance of the social responsibility concepts for the educational systems in the selected countries. For instance, Rauhansalo and Kvieska (2017) analyzed the significance of social studies and social subjects in the Finnish educational system and revealed that the Finnish National Board of Education identifies social studies as a critical element for the basics of democracy education, like equality, respect for human rights, social responsibility and freedom of opinions. Another example is the Teaching Personal and Social Responsibility model proposed by Hellison (2003).…”
Section: Findings: Manifestation Of Social Responsibility Through Citmentioning
confidence: 99%
“…In OECD PISA research (Geske et al, 2020), evidence is highlighted that students in Latvia feel they belong to their school less than OECD countries' average. The self-representation method may help the emotional rehabilitation of bullying victims in some cases (O'Brien & Dadswell, 2020), but collaboration between schools and the wider environment will improve students' understanding of how school life relates to real life (Rauhansalo & Kvieska, 2017). The results of another study (Lazar, 2013) show a significant connection between bullying and later antisocial behavior.…”
Section: School Climate and Civic Activitiesmentioning
confidence: 99%